Non-steroidal anti-inflammatory drugs and clinical outcomes in patients with COVID-19 - Zhang, Jing; Sheng, Hongguang; Tang, Xiaoyi; Xia, Panpan; Li, Zhangwang; Xu, Minxuan; Ma, Jianyong; Shen, Yunfeng; Yu, Peng; Liu, Xiao (Frontiers in Cellular and Infection Microbiology, 2022)
The use of non-steroidal anti-inflammatory drugs (NSAIDs) in patients with coronavirus disease 2019 (COVID-19) has raised great concerns. The effect of NSAIDs on the clinical status of COVID-19 remains in question. Therefore, we performed a post-hoc analysis from the ORCHID trial. Patients with COVID-19 from the ORCHID trial were categorized into two groups according to NSAID use. The 28-day mortality, hospitalized discharge, and safety outcomes with NSAIDs for patients with COVID-19 were analyzed. A total of 476 hospitalized patients with COVID-19 were included; 412 patients (86.5%) did not receive NSAIDs, while 64 patients (13.5%) took NSAIDs as regular home medication. Patients who took NSAIDs did not have a significant increase in the risk of 28-day mortality (fully adjusted: hazard ratio [HR]: 1.12, 95% CI: 0.52–2.42) in the Cox multivariate analysis. Moreover, NSAIDs did not decrease hospital discharge through 28 days (fully adjusted: HR: 1.02, 95% CI: 0.75–1.37). The results of a meta-analysis including 14 studies involving 48,788 patients with COVID-19 showed that the use of NSAIDs had a survival benefit (summary risk ratio [RR]: 0.70, 95% CI: 0.54–0.91) and decreased the risk of severe COVID-19 (summary: RR: 0.79, 95% CI: 0.71–0.88). In conclusion, the use of NSAIDs is not associated with worse clinical outcomes, including 28-day mortality or hospital discharge in American adult hospitalized patients with COVID-19. Based on current evidence, the use of NSAIDs is safe and should not be cautioned against during the COVID-19 pandemic. Ongoing trials should further assess in-hospital treatment with NSAIDs for patients with COVID-19.